Cultural Intelligence, Diversity Climate, and Employee Behavior: A Study of MNE Subsidiaries in China - Du, Juana; Wang, Rong; Jiang, Crystal (Journal of Comparative International Management)

(untitled) (Management Futures, 2023)
This study draws from the literature on workplace diversity, cultural intelligence, and creativity to examine the relationship between diversity climate and employees’ behaviors. With data collected from three multinational enterprise subsidiaries that operated in China for over 25 years, this study reveals that employees’ metacognitive cultural intelligence is positively related to their perceived diversity climate, leading to creative behavior and citizenship altruism behavior. In addition, this study examines an important interpersonal factor that is sensitive to the Confucius culture, harmony, and finds it directly impact motivational cultural intelligence. The mediating effect of harmony on the relationship between motivational cultural intelligence and employees’ altruism behaviors is also tested. This study contributes to the literature by investigating the organizational mechanisms underlying the role of cultural intelligence on employee behaviors in culturally diverse workplaces. Practical implications are also discussed.